Development of a Simple and Accurate Molecular Protocol Using 16SrRNA for Species-Specific Identification of Achromobacter spp. - Giulia Maria Saitta; Laura Veschetti; Rebecca Feletti; Angela Sandri; Marzia Boaretti; Paola Melotti; Maria Carelli; Maria M. Lleò; Giovanni Malerba; Caterina Signoretto (Pathogens)
The Achromobacter genus comprises 22 species and various genogroups. Some species with higher virulence or antibiotic resistance are more likely to cause chronic infections in people with cystic fibrosis (CF). Current identification methods often fail to accurately distinguish between the species or result in misidentifications due to biochemical similarities. This study aims to develop an accurate qPCR protocol for species-level identification that is applicable in clinical diagnostic laboratories. Whole-genome sequencing of clinical isolates from different Achromobacter species identified species-specific single-nucleotide polymorphisms (SNPs) in two 16S gene regions. Based on these SNPs, two sets of primers and qPCR probes were designed to generate unique identification profiles. Thermal profiles were optimized, and qPCR was performed on serial bacterial DNA dilutions to determine the detection limit (LOD). Four probes successfully identified three species: A. xylosoxidans, A. dolens, and A. insuavis. Two additional probes were designed for novel genotypes unrelated to publicly available sequences. The LOD ranged from 0.005 pg/µL to 1 pg/µL. Combined probes achieved 100% sensitivity, with specificity ranging from 97.95% to 100%. This qPCR protocol enables accurate species identification, overcoming the limitations of current methods, and represents a reliable tool for clinical diagnostics.